Millimeter wave band cavity resonators for magnetoresonance experiments - Tarapov, SI; Yildiz, F; Tuchkin, YA (Kluwer Academic/Plenum Publ, 2002)
Electrodynamical features of rectangular cavity resonators as experimental cells of Electron Spin Resonance spectrometer for the millimeter frequency band have been investigated. Measurements and analytical estimations of features of three types of resonators (film-wall type, diffraction grating-wall type, double-wall type) are presented. The advantages and imperfections of each design as well as recommendations for their applications in millimeter wave magnetospectroscopy are given.
Keywords: cavity resonator; millimeter wave band; electron spin resonance